3D scaffolds prepared from acylated chitosan applicable in skin regeneration – synthesis and characterization. Issue 1 (2nd January 2019) - Radwan-Pragłowska, Julia; Piątkowski, Marek; Janus, Łukasz; Bogdał, Dariusz; Matysek, Dalibor; Cablik, Vladimir
Abstract: Nowadays, burn wounds are one of the most emerging problems of medicine. Tissue engineering seems to be a promising solution since it enables new tissue formation on 3 D scaffolds. In this article, a novel strategy for N -acylated chitosan 3 D scaffolds obtainment method is presented. Biomaterials were synthesized according to Green Chemistry principles under microwave-assisted conditions using unsaturated fatty acid chlorides. Ready products were characterized over their physicochemical properties, morphology, mechanical, and biological properties. Performed analyses confirmed obtainment of N -acylated biomaterial with a very porous structure and enhanced durability. Prepared scaffolds were biodegradable and had a positive impact on mouse fibroblasts.